Progression through mitosis promotes PARP inhibitor-induced cytotoxicity in homologous recombination-deficient cancer cells - Pepijn M. Schoonen (Nature Portfolio, 2017)
Mutations in BRCA1 and BRCA2 render a cancer cell hypersensitive to PARP inhibitors but they can acquire resistance and relapse. Here the authors find that PARP inhibition leads to replication fork instability, cytokinesis failure and cell death, aiding our understanding of how inhibition leads to cytotoxic outcomes.